Double semilunar valve replacement in complex congenital heart disease using decellularized homografts. (16th July 2018) - Bobylev, Dmitry; Sarikouch, Samir; Tudorache, Igor; Cvitkovic, Tomislav; Söylen, Bahar; Boethig, Dietmar; Theodoridis, Karolina; Bertram, Harald; Beerbaum, Philipp; Haverich, Axel; Cebotari, Serghei; Horke, Alexander
Abstract: OBJECTIVES: Patients with complex congenital heart disease often require multiple reoperations, resulting in increased rates of operative morbidity and mortality. Decellularized heart valves (DHVs) have led to reduced reoperation rates compared with current other valve substitutes when used for pulmonary valve replacement and have also shown very auspicious early results in aortic valve replacement. The aim of the work was to analyse the outcome of a single-stage decellularized valve implantation in the aortic and pulmonary position. METHODS: A prospective follow-up of all patients who received a single-stage double semilunar valve replacement using DHV at our institution. RESULTS: Since 2011, 5 patients underwent combined semilunar valve replacement with DHV at our institution: two following a Ross procedure (31-year-old man and 38-year-old woman) and 3 after repair of the truncus arteriosus communis (2-year-old boy and 11-year-old and 16-year-old girls). All patients had undergone previous surgery. The Ross patients had preceding valve procedures, and the patients with truncus arteriosus communis had undergone 1 repair and subsequent operative procedures. Despite challenging operations (median bypass time 346 min, range 275–477 min; median cross-clamp time 229 min, range 140–307 min), there was no perioperative mortality or reoperations. Four of the patients were extubated within 24 h, and the other patient was extubated on postoperative day 2. During follow-up, a good semilunar valve and biventricular heart function was present in all 5 patients, and the New York Heart Association functional class was I for all the patients at the time of their latest follow-up (median 31 months, range 8–82 months). The mean echocardiographic gradient of decellularized aortic homografts was 5.4 ± 3.2 mmHg and 11.6 ± 4.2 mmHg for the decellularized pulmonary homografts. Valvular regurgitation was 0 or 0–I for all DHVs. CONCLUSIONS: A single-stage double semilunar valve replacement with DHV has shown promising early results in these 5 very complex cases, providing an additional surgical option after multiple preceding valve procedures in young patients.